2011
DOI: 10.1002/cjas.219
|View full text |Cite
|
Sign up to set email alerts
|

Virtuous Creativity: The Effects of Leader Behavioural Integrity on Follower Creative Thinking and Risk Taking

Abstract: Despite the preponderance of research concerning creativity and ethical leadership, the possibility of why and how a leader's ethical behaviour may stimulate follower creativity has not been examined. Employing an online experimental design, we applied a virtue ethics framework to examine associations between subordinates' perceptions of their leader's integrity and their intention to think creatively and to engage in risk taking. Subordinates' perceptions of their leader's behavioural integrity positively pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 49 publications
0
43
0
2
Order By: Relevance
“…Strictly speaking, behavioral integrity could include adherence to anti-social or evil values, but Palanski and Yammarino (2007) proposed and subsequent research (e.g., Leroy et al 2012b; has supported that behavioral integrity is associated with virtuous behavior. Behavioral integrity has been shown to be a parsimonious construct and a robust driver of outcomes such as trust in the leader and psychological safety (Palanski and Vogelgesang 2011), as well as an important mediator for the effects of authentic leadership (Leroy et al 2012a) and moderator for the effects of constructs such as supervisory guidance (Dineen et al 2006). It is important to note that behavioral integrity is typically ''in the eye of the beholder'' as an individual-level construct .…”
Section: Behavioral Integritymentioning
confidence: 98%
“…Strictly speaking, behavioral integrity could include adherence to anti-social or evil values, but Palanski and Yammarino (2007) proposed and subsequent research (e.g., Leroy et al 2012b; has supported that behavioral integrity is associated with virtuous behavior. Behavioral integrity has been shown to be a parsimonious construct and a robust driver of outcomes such as trust in the leader and psychological safety (Palanski and Vogelgesang 2011), as well as an important mediator for the effects of authentic leadership (Leroy et al 2012a) and moderator for the effects of constructs such as supervisory guidance (Dineen et al 2006). It is important to note that behavioral integrity is typically ''in the eye of the beholder'' as an individual-level construct .…”
Section: Behavioral Integritymentioning
confidence: 98%
“…Perhaps not surprisingly, virtue ethicists question the meaningfulness of empirically driven approaches (Fowers, 2008). Other self-instruments such as the Virtuous Leadership Scale (VLS; Sarros et al, 2006) focus on a single virtue only, as do many of the options for obtaining subordinatebased evaluations; for example, moral courage (Hannah and Avolio, 2010), professional moral courage (Palanski and Vogelgesang, 2011), behavioral integrity (Prottas, 2013) or benevolence (Wu and Tsai, 2012). Finally, the 34-item Virtue Ethical Character Scale (VECS; cf.…”
Section: Assessments Of Virtuous Leadership In Prior Researchmentioning
confidence: 99%
“…Virtue ethics, as one of the three leading moral philosophies (the others being deontology and teleology; Palanski and Vogelgesang, 2011), has its roots in both the ancient Greek civilization, especially in Aristotelianism (MacIntyre, 1984) and in Confucianism (Chan, 2003). In general, virtue ethics is "a system of ethical thought which considers the development and nurture of moral character as the best way to affect moral behavior and a moral society" (Palanski and Yammarino, 2009, p. 176).…”
Section: Introductionmentioning
confidence: 99%
“…Palanski and Vogelgesang (2011) conducted an online experiment and showed that followers' perceptions of leader's behavioral integrity positively predicted their intention to think creatively and to take risks via their sense of psychological safety. Gu, Tang and Jiang (2013) examined moral leadership in a Chinese context and found that the relationship between moral leadership and employee creativity was mediated by both employee identification with the leader and LMX.…”
Section: Ethical Leader Behaviorsmentioning
confidence: 99%